Plant invasion reduces density-dependent pollination but not florivory - Nicholas Sookhan; Shane Sookhan; Devlin Grewal; Thomas M. Onuferko; Marc W. Cadotte; J. Scott MacIvor (Oecologia, 2026)

Reduced soil multifunctionality and microbial network complexity in degraded and revegetated alpine meadows - Bobo Wu; Mingjun Ding; Hua Zhang; Adam Thomas Devlin; Peng Wang; Lu Chen; Yueju Zhang; Yang Xia; Jiawei Wen; Linshan Liu; Yili Zhang; Minhuang Wang (Journal of Environmental Management, 2023)

Multi-regional observations and validation of the M3 ocean tide - Adam Thomas Devlin; Jiayi Pan; Déborah Idier (Science China Earth Sciences, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Potential spawning grounds of phytophilic fish under a shifting hydrological regime in Poyang Lake, China - Qiyue Li; Xiaofeng Dai; Ying Liu; Adam Thomas Devlin; Geying Lai; Weiping Wang (Fisheries Management and Ecology, 2022)
The quality and effectiveness of fish spawning grounds are of great significance to the conservation of freshwater systems, and the distribution of spawning grounds is critical to clearly identify. This study combines a hydrodynamic model and satellite imagery to determine potential spawning grounds in the largest freshwater lake in China. Results revealed that the increase in vegetation in Poyang Lake led to an expansion of potential spawning grounds towards the centre of the lake due to a water level decrease since 2000. The mean spawning grounds area in Poyang Lake declined from 482.51 to 814.40 km 2 after 2005 and average bathymetry decreased from 12.29 to 10.49 m. The current nature reserve holds 18.26% of the total spawning grounds, while sub‐lakes hold 34.02% of the total. The constant area of spawning grounds under typical scenarios should be the baseline for future conservation.

Can sex-specific consumption of prey be determined from DNA in predator scat? - Brittany S. Balbag; Austen C. Thomas; Robert H. Devlin; Dietmar Schwarz (Conservation Genetics Resources, 2019)

Velocity Curvature Index: a Novel Diagnostic Biomarker for Large Vessel Occlusion - Samuel G. Thorpe; Corey M. Thibeault; Seth J. Wilk; Michael O’Brien; Nicolas Canac; Mina Ranjbaran; Christian Devlin; Thomas Devlin; Robert B. Hamilton (Translational Stroke Research, 2019)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)

Food Shortage Causes Differential Effects on Body Composition and Tissue-Specific Gene Expression in Salmon Modified for Increased Growth Hormone Production - Jason Abernathy; Stéphane Panserat; Thomas Welker; Elisabeth Plagne-Juan; Dionne Sakhrani; David A. Higgs; Florence Audouin; Robert H. Devlin; Ken Overturf (Marine Biotechnology, 2015)

A Case of Abrin Toxin Poisoning, Confirmed via Quantitation of l-Abrine (N-Methyl-l-Tryptophan) Biomarker - Joe Valentine Wooten; Christopher T. Pittman; Thomas A. Blake; Jerry D. Thomas; John J. Devlin; Renee A. Higgerson; Rudolph C. Johnson (Journal of Medical Toxicology, 2014)